Implementasi Program Kartu Pelaku Usaha Kelautan dan Perikanan bagi Nelayan di Pasie Nan Tigo Kota Padang - Saputra, Affendi; Magriasti, Lince (PUBLICNESS: Journal of Public Administration Studies, 2024)
The legal basis for the implementation of the marine and fisheries business card program for fishermen in pasie nan tigo is PERMEN KP Number 41 of 2022. This card has many benefits, especially for fishermen, namely one of the requirements for purchasing fuel. However, in the implementation of the KUSUKA card program for fishermen in Pasie Nan Tigo, there are still few fishermen who hold KUSUKA cards. In addition, only fishermen who are members of groups created by the fisheries service get KUSUKA cards, so other small fishermen cannot get them. The purpose of this study is to see how the implementation of the marine and fisheries business actor card program for fishermen in Pasie Nan Tigo Padang City and to find out the obstacles in implementing this program. This research uses a qualitative approach. The results of the study indicate that the implementation of this card program for fishermen in Pasie Nan Tigo Padang City has been implemented but not well implemented and there are still some shortcomings when viewed from the following aspects Communication has been done, but not yet effective. Second, from the aspect of resources, it is quite good but non-human resources are also still lacking, namely the absence of wifi. From the aspect of disposition or the attitude of the implementer here is good. In terms of bureaucratic structure, it has gone well.